Hydrogen generation from glucose catalyzed by organoruthenium catalysts under mild conditions. Issue 30 (30th March 2017) - Zhan, Yulu; Shen, Yangbin; Li, Shuping; Yue, Baohua; Zhou, Xiaochun
Abstract : Here, we describe a catalytic reaction system where H2 can be produced from glucose using a homogeneous catalyst. Abstract : Concerns about the depletion of fossil fuel reserves and environmental pollution make hydrogen an attractive alternative energy source. Here, we first describe a catalytic reaction system that produces H2 from glucose using a homogeneous catalyst [( p -cymene)Ru(NH3 )]Cl2 with the maximum TOF = 719 h −1 at 98 °C and an initial pH = 0.5.